2017
DOI: 10.1515/amtm-2017-0010
|View full text |Cite
|
Sign up to set email alerts
|

The influence of geometric imperfections on the stability of three-layer beams with foam core

Abstract: A B S T R A C TThe main objective of this work is the numerical analysis (FE analysis) of stability of three-layer beams with metal foam core (alumina foam core). The beams were subjected to pure bending. The analysis of the local buckling was performed. Furthermore, the influence of geometric parameters of the beam and material properties of the core (linear and non-linear model) on critical loads values and buckling shape were also investigated. The calculations were made on a family of beams with different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…When analyzing thin-walled structures, the effect of imperfection is important. The effect of geometric imperfections on the stability of three-layer beams is described in the paper [12].…”
Section: Introductionmentioning
confidence: 99%
“…When analyzing thin-walled structures, the effect of imperfection is important. The effect of geometric imperfections on the stability of three-layer beams is described in the paper [12].…”
Section: Introductionmentioning
confidence: 99%
“…These defects have a great influence on mechanical behaviors, causing a decrease in the buckling capacity of tubes under axial loading [3,7]. In addition, many experimental studies have shown that buckling appeared earlier than estimated because of initial imperfections, such as in the case of I-sections [6,8], box sections [3,9,10], equal angle columns [11][12][13], T-sections [14], circular sections [15,16], and C-sections [17][18][19] for steel structures or concrete structures [20][21][22], composite structures [23][24][25], and alloy structures [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, analytical solutions often demonstrate a limitation as the structures are simplified with regular geometry. In the case of more complex structures, the numerical finite element technique has been widely applied to investigate the influence of initial imperfections on the buckling behavior of compression members, such as sigma section members [17], I-section steel columns wrapped by carbon fibers [24], cylindrical pipes made by carbon fiber-reinforced plastic material [23], braced columns [33], and multi-layer beams [25]. However, finite element analysis of buckling problems is mainly based on commercial software, for instance, ANSYS [7,19], ABAQUS [23,27], and NASTRAN [17].…”
Section: Introductionmentioning
confidence: 99%